The simulation of the dust grain movement by sediment transport model around mining area in northern Sweden - Huang, Yi; Al-Ansari, Nadhir; Knutsson, Sven; Jia, Qi (Luleå tekniska universitet, Geoteknologi, 2012)
A simple sediment transport model has been utilized to simulate the dust grain movement in the area flow. The transport model can be used as a tool to estimate the dust grain transport situation in a mining area with consideration of the local topographical profile. The case study of the local dust characteristics survey proves the model works fairly well compared to the field calibration. Validerad; 2012; 20120913 (nadhir)